Tafsir Ayat-Ayat Teologis dalam al-Muharrar al-Wajiz: Studi Kritis Atas Tuduhan I’tizal terhadap Ibnu Athiyyah - Subi Nur Isnaini (Jurnal Studi Al-Qur'an, 2021)
This paper discusses the Ibn Athiyyah positions towards the concept of Muktazilah theology in his exegesis al-Muharrar al-Wajiz. Although Ibn Athiyyah is an interpreter who has Asy'ariyah school of thought, some scholars such as Ibn Taimiyyah (d. 728), Ahmad bin Hajar al-Haitami (d. 973) and Ibn 'Arafah (d. 803 H) have stated that Ibn Athiyyah interpretation has included the concept of Muktazilah theology. More over, al-Haitami also quoted Ibn 'Arafah's comment that the interpretation of Ibn Athiyyah was more worrying for beginner students than al-Kasysyaf, because al-Zamakhsyari, the author of al-Kasysyaf, was already known as a Mu’tazili, different with Ibn Athiyyah. This research is a type of qualitative research with a library research approach. By using a descriptive analysis, this paper explores Ibn Athiyyah‘s interpretation of the verses which are the evidence for the concept of Muktazilah theology or what is often referred to as al-Ushul al-Khamsah. The results of this study shows that the accusation of i'tizal aimed to Ibn Athiyyah is not true, because his interpretation of theological verses shows that Ibn Athiyyah always approves and justifies the Ash'ariyyah opinions. More over, on several occasions Ibn Athiyyah has refuted the opinions and arguments that used Muktazilah to affirm their theological concept.